Normalizing homophobic discourse. Bioethical considerations - Sevilla González, María de la Luz; Álvarez Licona, Nelson Eduardo (Acta Bioethica, 2006)
The homophobia is present in all social discourses, but we do not realize it due to the normalization of certain rejection behaviors against homosexual persons. This paper analyzes specifically the homophobic discourse of health care personnel. The professional ethics dictates this personnel treats with respect and dignity to all patients. Nevertheless it has been proved that there are some prejudice attitudes in health care centers which diminish the possibility of health care assistances to patients and generate a poor and distrusted relationship between the health care professional and the patient.